3D printing of PDC-SiOC@SiC twins with high permittivity and electromagnetic interference shielding effectiveness. Issue 11 (September 2021) - Yang, Wenqiang; Yang, Dou; Mei, Hui; Yao, Li; Xiao, Shanshan; Yao, Yongtao; Chen, Chao; Cheng, Laifei
Highlights: Twin SiC nanowires were successfully fabricated in 3D printed SiOC ceramic. The ceramic exhibited high permittivity in X-band, which is beneficial for the electromagnetic shielding effectiveness. The ceramic possess good mechanical property, which indicates its potential in practical application. Abstract: Effective electromagnetic interference (EMI) shielding requires materials with high permittivity. The current study reports 3D printed polymer-derived SiOC ceramics (PDC) modified with SiC nanowires (SiCnw ) exhibiting both high real and imaginary parts of permittivity within X-band. SEM results indicated that a large number of pores and cracks exist in the SiOC, and twinned SiCnw were uniformly grown among them along with the existence of graphite microcrystals when the sintering temperature was 1500 ℃. The real part of permittivity ranged from 16.6 to 28.9 while the imaginary part from 31.7 to 34.2 in X-band. The EMI total shielding effectiveness (SET ) of the ceramics could reach 34.7 dB with absorption loss (SEA ) of 29.3 dB and reflection loss (SER ) of 5.4 dB. Meanwhile, the 3D printed PDC-SiOC ceramics at 900 ℃ sintering temperature possess certain mechanical properties with the magnitude of compressive strength being 12.57 MPa.